Detection of desirable areas for urban growth through GIS and OWA: the case of Culiacan and Navolato - Uriarte Adrián, José Jesús; Plata Rocha, Wenseslao; Romero Andrade, Rosendo; Corrales Barraza, Gabriela; Beltrán González, José C.; Remond Noa, Ricardo (CIENCIA ergo-sum; Vol. 27 Núm. 2 (2020): CIENCIA ergo-sum (julio-octubre 2020)DO - 10.30878/ces.v27n2a6, 2020)
Due to an accelerated growth of artificial surfaces, an increasing interest in the changes on land use has been detected in the last decade, making it necessary to propose models able to create plans of optimal and sustainable development. The goal of this work is to identify the potentially most suitable spaces for urban growth, through geospatial simulations which integrate the Geographic Information Systems and OWA (Ordered Weighted Average). We propose a sensitivity analysis methodology to the results in order to assess their robustness with respect to the input values’ weights variability, based on histograms and distances classification. Finally, the selection proposal shows a considerable percentage according to the planned area.